ENVIRONMENTAL TECHNOLOGIES AND IMPACTS ON ECONOMIC AND FINANCIAL PERFORMANCE: THE CASE OF CELULOSE IRANI S/A - Lazzarotti, Fábio; Sehnem, Simone; Pavão, Yeda Maria Pereira; Alberton, Anete; Marinho, Sidnei (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
This article analyzes the impact of environment technologies in the financial performance of company’s pulp and paper. Among the investments it was delimited in this study, two projects implemented by the company: the plant cogeneration power station and upgrading of sewage treatment station. To collect data, document analysis and content was conducted by means of descriptive and quantitative procedure, based on secondary data available in sustainability reporting and financial statements. Environmental investments seem to have favorably impacted the financial performance of the organization, taking into account only the indicators of economic value and cash flow, in particular MVA and EBITDA despite the international financial crisis. However, there is evidence that environmental investments are in line with the policy to mitigate environmental impacts during the production process of the company Irani. This is proved by the results obtained so far, which shows that the CDM projects since its consolidation enabled a reduction in the emission of approximately 200 000 tonnes of CO2 a year.